Intrahepatic Cholangiocarcinoma Presenting as the Budd-Chiari Syndrome: A Case Report and Literature Review - Joanna K Law; Jenny Davis; Anne Buckley; Baljinder Salh (Canadian Journal of Gastroenterology)
Intrahepatic cholangiocarcinoma, an increasingly recognized primary tumour of the liver, is associated with a very poor prognosis. A patient with this tumour who presented with Budd-Chiari syndrome (the first to the authors' knowledge in Western literature and only the third patient overall) secondary to extensive thrombosis in his inferior vena cava extending from the right atrium down to his iliac vessels is described. Neither curative nor palliative intervention was deemed to be an option in this patient, who deteriorated rapidly while on anti-coagulants. Postmortem examination confirmed the radiological findings, and histological analysis revealed characteristic appearances of this tumour within the biliary tree and invasion into the inferior vena cava. Furthermore, biliary dysplasia, which can be a precursor to this cancer, was also noted within some of the bile ducts.